INTERNALISASI NILAI-NILAI AGAMA ISLAM UNTUK MEMBENTUK SIKAP DAN PERILAKU SISWA SEKOLAH DASAR ISLAM TERPADU AL-MUKMINUN NGRAMBE NGAWI - Wibawati Bermi (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2016)
In this study has the sole purpose to describe the curriculum applied in Integrated Islamic Primary School Al-Mukminun Ngrambe Ngawi, the process of internalizing the values of the Islamic religion in the attitudes and students behavior, and the relationship process of internalization of values of Islam with the formation of attitudes and behavior.Implementation of this research using naturalistic qualitative approach, and the main subject is the vice-principal, teacher / homeroom, students and parents. The results showed as follows: 1) Curriculum Integrated Islamic Primary School Al-Mukminun using Ministry of education curriculum, the curriculum of the Ministry of Religious Affairs, and institutional curriculum. 2) The process of internalization of Islamic values on students' attitudes and behavior approach: persuade and accustom, raise awareness, and show discipline and uphold the rules of the school. Teaching methods include modeling, ibrah with storytelling, speech and mau'zah (suggestion), question and answer, demonstration, habbit formations, field / real experience, assignments, outbound, singing. 3) Use of the model curriculum and internalization of values religious values of Islam proved to be shaping students' attitudes and behaviors of obedience to God, both to fellow beings and nature, a good personality, responsibility, BRAVEMAN, think Critically andÂ  civillize healthy behavior.Keywords: Islamic values, attitudes and behavior, Integrated Islamic Primary School Al-Mukminun